Pengembangan Media Pembelajaran Program Linier Berbasis Geogebra di STMIK STIKOM INDONESIA - Ni Wayan Suardiati Putri; Kadek Suryati (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
The type of research conducted is development research. The aim of this research is to produce a valid and practical learning media GeoGebra based program at STMIK STIKOM Indonesia. The model of development used is Model Plomp consisting of (1) initial investigation stage, (2) design stage, (3) realization stage/construction, (4) test, evaluation and revision, and (5) implementation. The research is only up to a limited trial, not implementation. Validity testing of content, design and media is carried out by experts in their fields. While practicality tests are measured through students' responses to the use of media. The results showed that the learning media were classified as valid and practical with an average value of validity test on content, design, and media respectively were 3.78, 3.43, and 3.57. As for the value of practicality tests conducted by students is 85.86%.